Shoulder pathology on magnetic resonance imaging in asymptomatic elite-level rock climbers - Cooper, J. D.; Seiter, M. N.; Ruzbarsky, J. J.; Poulton, R.; Dornan, G. J.; Fitzcharles, E. K.; Ho, C. P.; Hackett, T. R. (Orthopaedic Journal of Sports Medicine, 2022)
Background: The prevalence of findings on shoulder magnetic resonance imaging (MRI) is high in asymptomatic athletes of overhead sports. Purpose/Hypothesis: The purpose of this study was to determine the prevalence of atypical findings on MRI in shoulders of asymptomatic, elite-level climbers and to evaluate the association of these findings with clinical examination results. It was hypothesized that glenoid labrum, long head of the biceps tendon, and articular cartilage pathology would be present in >50% of asymptomatic athletes. Study Design: Cross-sectional study; Level of evidence, 3. Methods: A total of 50 elite climbers (age range, 20-60 years) without any symptoms of shoulder pain underwent bilateral shoulder examinations in addition to dedicated bilateral shoulder 3-T† MRI. Physical examinations were performed by orthopaedic sports medicine surgeons, while MRI scans were interpreted by 2 blinded board-certified radiologists to determine the prevalence of abnormalities of the articular cartilage, glenoid labrum, biceps tendon, rotator cuff, and acromioclavicular joint. Results: MRI evidence of tendinosis of the rotator cuff, subacromial bursitis, and long head of the biceps tendonitis was exceptionally common, at 80%, 79%, and 73%, respectively. Labral pathology was present in 69% of shoulders, with discrete labral tears identified in 56%. Articular cartilage changes were also common, with humeral pathology present in 57% of shoulders and glenoid pathology in 19% of shoulders. Climbers with labral tears identified in this study had significantly increased forward elevation compared with those without labral tears in both active (P = .026) and passive (P = .022) motion. Conclusion: The overall prevalence of intra-articular shoulder pathology detected by MRI in asymptomatic climbers was 80%, with 57% demonstrating varying degrees of glenohumeral articular cartilage damage. This high rate of arthritis differs significantly from prior published reports of other overhead sports athletes.